Intellectual capital reporting and corporate characteristics of public-listed companies in Malaysia. - Foong, Soon Yau; Loo, Sin Chun; Balaraman, Rajeswary (Emerald Group Publishing Limited, 2009)

(untitled)
This study examines the extent and nature of voluntary intellectual capital (IC) disclosure by public-listed companies in Malaysia and how the disclosure may be explained by the economics or other rationale of corporate disclosure. Those intangible assets that are required to be disclosed under the extant accounting standards were specifically excluded from this study. The top 30 and the bottom 30 companies were selected from the list of top 100 largest public-listed companies by market capitalization at the end of 2003. Content analysis was used to measure the extent of voluntary IC disclosure in the 2003 annual reports of the selected companies. This study found that the voluntary disclosure of IC information is generally not extensive among the publiclisted companies in Malaysia and narrative description of their IC attributes is the most often adopted format. The findings suggest that the IC disclosure behaviour of the sample companies may be explained based on both economic and non-economic rationale. Implications of the findings are discussed.